Evaluacion De Dos Instrumentos De Medicion En La Determinación Del Área Basal En Pinus Radiata - Vásconez, Norma Lara; Morocho, Janneth; Lara, Santiago; Guadalupe, Oscar; Chavez, Keilly; Vega, Alex Espin, Holger; Coveña, Karina (European Scientific Journal, ESJ, 2017)
This study compares the diameter of data obtained from utilizing two measuring instruments (the caliper and diameter tape). This instrument is the two most commonly used instruments for measuring tree diameters in forest inventory procedures. The measurement of diameter has a high implication in the estimation of the basal area and stand volume. It is therefore imperative to ensure accurate measurement of the diameter of trees in a stand. This work evaluated data taken with these two diameter measuring instruments. In order to evaluate the performance of the measuring instruments, parallel measurement of the diameter at breast height (DBH) of a sample of Pinus radiata trees in a plantation were measured. Also, the basal area of the stand was determined for both instruments. It was concluded through the analysis of variance (ANOVA) that there is no significant (p =0.958) difference between the averages of the calculated basal areas from the diameter measurements obtained by the diameter tape and the caliper. The estimated value from the diameter tape was 0,04190829, while the caliper was 0,04145599. Thus, the use of the two measurement tools led to similar results in the calculation of the cross-sectional areas of pine trees measured at breast height.